The use of «Erectron» apparatus after fallopian tube surgery - I. I. Diamant; A. A. Radionchenko (Бюллетень сибирской медицины)
In order to increase the efficiency of surgery at fallopian tube pathology there has been proposed a method of medical rehabilitation with the use of «Erectron» apparatus (autonomous electrical stimulator of gastrointestinal tract — AES GIT). In 1998—2002 in Tomsk Research Institute of balneology and physiotherapy 100 women at the age of 18—39 (26,3 ± 4,1) have undergone a cure with «Erectron» AES GIT. Postsurgical period has been 2,9 ± 0,2 months. After the course of electrostimulation there has been registered an improvement of gynaecological state, blood circulation and functional activity of fallopian tubes. Efficiency of treatment immediately after the treatment has been 84%. Pregnancy beginnings after 18 months — in 39% cases (control — 15%). The proposed method is simple, safe and easy of use and access. It can be used in physiotherapy departments and at the absence of such — as a little physiotherapy — in postsurgical room, medical assistant’s post and rural hospital.